The simultaneous equations are:
![\begin{gathered} -2x+7y=-23 \\ 6x-7y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/btte26kf60vrap7hcargg9uttlw42e22fw.png)
Since, the unknown y has the same co-efficient across the two(2) equations, we can eliminate it directly.
Thus, we have:
![\begin{gathered} -2x+7y=-23 \\ 6x-7y=-1 \\ ----------- \\ -2x+6x=-23-1 \\ 4x=-24 \\ x=(-24)/(4) \\ x=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f6qder3168q3bhoya7hdmvbki311afcbty.png)
To find y, substitute for x = -6 into any of the equations.
Thus, we have:
![\begin{gathered} \text{from equation i)} \\ -2x+7y=-23 \\ -2(-6)+7y=-23 \\ 12+7y=-23 \\ 7y=-23-12 \\ 7y=-35 \\ y=-(35)/(7) \\ y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4c9arip0jw5h0nafds0fwfepgxnt9lwmqx.png)
Hence, the correct option is option A